Analisis Break Even Point dan Margin of Safety Sebagai Alat Perencanaan Laba Pada Usaha Tahu Sumber Mulya Kota Bengkulu - Safitri, Wulan; Herlin, Herlin; Rahman, Abdul (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2024)
The purpose of this study was to determine the application of BEP and MOS as a profit planning tool in the Usaha Tahu Sumber Mulya  in Bengkulu city. The data collection method used is unstructured interviews and documentation with qualitative and quantitative analysis methods using Break Even Point analysis. The results of the  research, BEP the contribution ratio per unit of tofu was 41% with a business profit rate of 35.3% with a margin of safety of 86.1%. While the where the contribution ratio per unit of tofu was 49.2% with a business profit level of 44.1%, the level of security or margin of safety in 2022 was 89.8%.  The use of BEP and Safety stock calculation provides an overview of the Usaha Tahu Sumber Multa in Bengkulu City, you can see the BEP for tofu production and safety stock in the warehouse, this is so that the production process continues and obtain the desired profit .